2010
DOI: 10.1007/s12237-010-9336-8
|View full text |Cite
|
Sign up to set email alerts
|

Microzooplankton Grazing in Green Water—Results from Two Contrasting Estuaries

Abstract: We measured seasonal variations in microzooplankton grazing in Long Island Sound (LIS) and San Francisco Bay (SFB). There was consistent evidence of nutrient limitation in LIS, but not SFB. We found higher chlorophyll a concentrations in LIS compared with SFB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
6
23
0
Order By: Relevance
“…The growth rates were also similar to those found in estuaries in other regions (Murrell and Hollibaugh 1998;Calbet and Landry 2004;York et al 2010). Calbet and Landry (2004) summarized results from dilution experiments in 66 studies from coastal, oceanic, and estuarine habitats and found that in estuarine systems the mean community (chl a) growth rate was 0.97 + 0.07/d and the mean grazing rate was 0.53 + 0.04/d (n=136).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The growth rates were also similar to those found in estuaries in other regions (Murrell and Hollibaugh 1998;Calbet and Landry 2004;York et al 2010). Calbet and Landry (2004) summarized results from dilution experiments in 66 studies from coastal, oceanic, and estuarine habitats and found that in estuarine systems the mean community (chl a) growth rate was 0.97 + 0.07/d and the mean grazing rate was 0.53 + 0.04/d (n=136).…”
Section: Discussionsupporting
confidence: 83%
“…This result has been observed in many studies using the dilution method in a variety of environments (Landry and Hassett 1982;Landry et al 1984;Paranjape 1987;Gifford 1988;Kamiyama 1994;Murrell and Hollibaugh, 1998;Kim et al 2007;York et al 2010). Non-significant grazing has been attributed to high variability in the method due to the small sample number used in the dilution series (Schmoker et al 2013).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However the dilution method has known limitations e.g. non-linear response (Paterson et al 2008, York et al 2010 or nutrient depletion (Landry and Hassett 1982). Nonlinear responses were not observed in this study, and the higher nutrient concentrations in our samples as well as the shorter incubation time enabled us to complete the dilution experiments 10 before nutrient depletion sets in.…”
mentioning
confidence: 77%
“…The interaction between grazers and viruses is further complicated by the fact that the viruses of microzooplankton can lyse grazers (Garza & Suttle 1995), while grazers can consume viruses (Gonzalez & Suttle 1993, Miki & Jacquet 2008. Although many studies have documented strong relationships between biomass, growth and grazing (Juhl & Murrell 2005, PalomaresGarcía et al 2006, Putland & Iverson 2007, York et al 2010), other studies have indicated an uncoupling of these variables (Lehrter et al 1999, First et al 2007, Williams et al 2008, Ory et al 2010, Landry et al 2011). Grazing and/or viral lysis can exhibit patterns different from those of growth, over time or across space, resulting in an uncoupling of the processes.…”
Section: Introductionmentioning
confidence: 99%